Evaluation of a Cold Thermal Energy Storage System Using Alternative Refrigerants - Alshaibani, Salah Ali (2016)
A Master of Science thesis in Mechanical Engineering by Salah Ali Alshaibani entitled, "Evaluation of a Cold Thermal Energy Storage System Using Alternative Refrigerants," submitted in May 2016. Thesis advisor is Dr. Saad A. Ahmed and thesis co-advisor is Dr. Mohamed A. Gadalla. Soft and hard copy available.